2005
DOI: 10.1002/adma.200401286
|View full text |Cite
|
Sign up to set email alerts
|

New, Highly Ion‐Conductive Crystals Precipitated from Li2S–P2S5 Glasses

Abstract: very high saturation fields, similar to the parent powders. This implies that these submicrometer laminated cores can be used in high-power applications where excitation fields are large.In conclusion, we have successfully fabricated Fe/SiO 2 submicrometer laminates that have lateral dimensions of a few to several hundred micrometers and submicrometer thicknesses. The sheet structure is retained during the consolidation, giving rise to laminated soft Fe cores. High-frequency measurements show that the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
638
5
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 818 publications
(661 citation statements)
references
References 13 publications
16
638
5
2
Order By: Relevance
“…A high-temperature phase, such as α-AgI (Ag + superionic conductor) 25,26 or Li 7 P 3 S 11 (Li + superionic conductor) 16,17 , with a high ionic conductivity precipitates as the first crystal from a supercooled liquid above the glass transition temperature. This is the first time for sodium ion conductors that cubic Na 3 PS 4 has been stabilized as a high-temperature phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-temperature phase, such as α-AgI (Ag + superionic conductor) 25,26 or Li 7 P 3 S 11 (Li + superionic conductor) 16,17 , with a high ionic conductivity precipitates as the first crystal from a supercooled liquid above the glass transition temperature. This is the first time for sodium ion conductors that cubic Na 3 PS 4 has been stabilized as a high-temperature phase.…”
Section: Discussionmentioning
confidence: 99%
“…We have studied Li + ion conducting electrolytes and found that solid sulphide electrolytes made from the system Li 2 S-P 2 S 5 have a high conductivity and a wide electrochemical window 16,17 , making them suitable for all-solid-state lithium secondary batteries that have excellent cycling and rate performances [18][19][20][21] .…”
mentioning
confidence: 99%
“…such as Li 3 PS 4 and Li 10 SnP 2 S 14 ) available, where targeted structural chemistry might lead to the desired properties. 4,[77][78][79][80][81][82][83][84] …”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…The 70Li 2 S·30P 2 S 5 (mol %) glass-ceramic showed the highest conductivity of 3.2 © 10 ¹3 S cm ¹1 at room temperature in lithium ion conductors reported so far. 9) We found that a superionic conducting Li 7 P 3 S 11 crystal was precipitated in the 70Li 2 S·30P 2 S 5 (mol %) glass-ceramic. The Li 7 P 3 S 11 phase crystallized in a triclinic cell, space group P-1, a = 12.5009(3) ¡, b = 6.03160(17) ¡, c = 12.5303(3) ¡, ¡ = 102.845(3)°, ¢ = 113.2024(18)°, £ = 74.467(3)°.…”
Section: Introductionmentioning
confidence: 99%